Endocannabinoid signaling regulates the reinforcing and psychostimulant effects of ketamine in mice - Wei Xu (Nature Portfolio, 2020)
Ketamine is used for sedation and treatment of depression, but is also a drug of abuse. Here the authors show that ketamine modulates the endocannabinoid system in mice, and that this may contribute to its psychoactive effects.